Are Dysregulated Inflammatory Responses to Commensal Bacteria Involved in the Pathogenesis of Hepatobiliary-Pancreatic Autoimmune Disease? An Analysis Using Mice Models of Primary Biliary Cirrhosis and Autoimmune Pancreatitis. (15th June 2011) - Yanagisawa, Naoko; Haruta, Ikuko; Kikuchi, Ken; Shibata, Noriyuki; Yagi, Junji
Abstract : The etiopathogenesis of many autoimmune disorders has not been identified. The aim of this paper is to focus on the involvement of bacterial exposure in the pathogenesis of primary biliary cirrhosis (PBC) and autoimmune pancreatitis (AIP), both of which are broadly categorized as autoimmune disorders involving hepatobiliary-pancreatic lesions. Avirulent and/or commensal bacteria, which may have important role(s) as initiating factors in the pathogenesis of autoimmune disorders such as PBC and AIP, will be emphasized.